Synthesis, crystal structure, hirshfeld surface analysis, molecular docking and molecular dynamics studies of novel olanzapinium 2,5-dihydroxybenzoate as potential and active antipsychotic compound - V. Natchimuthu; Mohnad Abdalla; Manasi Yadav; Ishita Chopra; Anushka Bhrdwaj; Khushboo Sharma; S. Ravi; Krishnan Ravikumar; Khalid J. Alzahrani; Tajamul Hussain; Anuraj Nayarisseri (Journal of Experimental Nanoscience, 2022)
The antipsychotic drug Olanzapine was crystallized with aromatic acid, 2,5-dihydroxybenzoic acid in isopropyl alcohol by slow evaporation which led to the formation of olanzapinium 2,5-dihydroxybenzoate crystalline salt. The structure of the compound was characterized by 1H-NMR, 13C-NMR, and single-crystal X-ray diffraction analysis. The Hirshfeld analyses were performed to quantify the order and nature of intermolecular interactions in the crystal network. Employing computational approaches, the compound was tested for its affinity against antipsychotic activity by molecular docking and molecular dynamic simulation to attest the conformational stability over time step of 100 ns. Besides, bioactivity and ADMET properties were also predicted to ratify the result. The compound asserted neither carcinogenic nor mutagenic activity and has high oral bioavailability. Hence, this synthesized novel compound Olanzapinium 2,5-dihydroxybenzoate recognized in the study possesses high potential as an effective antipsychotic compound, and can further be examined for its efficiency by in vivo studies. The synthesized compound was submitted to NCBI PubChem database using accession substance ID: 441329256. The crystal structure was submitted to CCDC (Cambridge Crystallographic Data Centre) with submission ID: 2010899.